Soc 274- Social Statistics - Brashears, Matthew E. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The primary objective of this course is to introduce students to the concepts ofstatistical analysis. Statistics are a way to describe the world, much like a language, andthis course is intended to teach you how to speak that language, and understand itwhen it is spoken to you. Statistics are used in everything from advertisements, topolitical speeches, to sports. An understanding of statistics is, therefore, essential tobeing a literate, empowered, adult.Beyond that, statistics allow us to see the world with more than simply our owneyes. Statistics can allow us to pluck certainty from the vapor of possibility, providinginsight we couldn’t get anywhere else. While completion of prerequisites with the mathdepartment is necessary for this course, this is not a math class in the traditional sense.This class focuses on teaching you to use mathematics to answer substantivequestions, and on learning how to interpret what the math is telling you.By the end of class students should have an understanding of what statisticsare, the limitations of statistical analysis, possess the skills to interpret statistics, and be capable of conducting certain types of analyses themselves.